Selling Beaver Skins in North America and Europe, 1720-1760: The Uses of Fur-Trade Imperialism - Wien, Thomas (Journal of the Canadian Historical Association / Revue de la Société historique du Canada)

(untitled) (The Canadian Historical Association/La Société historique du Canada, 1990)
AbstractHistorians have tended to assume that, during the last decades of French rule in Canada, competition in the fur trade and the imperial contest in North America ran along the same lines. The posts of the rival empire on Hudson Bay or south of Lake Ontario are thought to have posed the main threat to the fortunes of the Montreal-based traders established in the heart of Indian lands. This article assesses the evidence for price competition between such distant antagonists in the trade in beaver. Owing to the Compagnie des Indes' pricing policies, this commodity usually fetched a lower price in the French trading system than it did in the one centred on London. There is little sign of a response in the distribution of beaver receipts to changes in the intercolonial price differential. This suggests that Canadian merchants exaggerated the force of foreign competition in order to lend weight to their appeals to the state for an increase in the price of beaver. The paper concludes that the obsession with the external foe, which the official sources have transmitted to historians, has obscured the internal dynamic of the Canadian fur trade during these years.